5x-7=7x+6

Simple and best practice solution for 5x-7=7x+6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5x-7=7x+6 equation:


Simplifying
5x + -7 = 7x + 6

Reorder the terms:
-7 + 5x = 7x + 6

Reorder the terms:
-7 + 5x = 6 + 7x

Solving
-7 + 5x = 6 + 7x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-7x' to each side of the equation.
-7 + 5x + -7x = 6 + 7x + -7x

Combine like terms: 5x + -7x = -2x
-7 + -2x = 6 + 7x + -7x

Combine like terms: 7x + -7x = 0
-7 + -2x = 6 + 0
-7 + -2x = 6

Add '7' to each side of the equation.
-7 + 7 + -2x = 6 + 7

Combine like terms: -7 + 7 = 0
0 + -2x = 6 + 7
-2x = 6 + 7

Combine like terms: 6 + 7 = 13
-2x = 13

Divide each side by '-2'.
x = -6.5

Simplifying
x = -6.5

See similar equations:

| 58=10x+8 | | 64x^4-27x=0 | | 11.5-8.5= | | 0=x^2-21x+24 | | 8-0.5(x+3)=0.25(x+-1) | | -(4-m)=10 | | 6=-4k+2 | | 20y+2=46 | | 1.33*4=y | | s*7-17=137 | | x^2+x+m-1=0 | | 5(x+3)-3=2(x+8) | | 43-4=y | | 9h-16=74 | | 9m-15=58 | | 5n^2+7n=-2 | | 8x+12y-20= | | 40+16x= | | 3(25-10h+h^2)-20+4h-(75-20)= | | 15x-28= | | 0=x^2-16x-225 | | 6x+27= | | x^7=65 | | 4.9x^2-20x=0 | | 8+(y+2)=4(y-3) | | x+(x*0.25)=500000 | | 3n+4-4=n+20 | | 4t^2-9s^2=0 | | lnx^2-6lnx+5=0 | | (5x-2)-(3x-1)=(4x+3)-(5x-2) | | 7(-1+h)-5(-1)= | | 2lnx+ln(2x-3)=ln(3x-2) |

Equations solver categories